2013
DOI: 10.1002/pen.23672
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal properties and material characteristics of PVC and wood/PVC composites doped with carbamate-based fungicides

Abstract: Antifungal properties of polyvinylchloride (PVC) and wood/PVC composites (WPVC) were studied with two different fungicides through disk diffusion and dry weight techniques against Aspergillus niger as a testing fungus. Three different types of woods, including Xylia kerrii Craib & Hutch.(XK), Hevea brasiliensis Muell.(HB), and Mangifera indica Linn.(MI), were used. The disk diffusion results revealed that the addition of 3‐iodopropinyl‐N‐butylcarbamate (IPBC) in the PVC and WPVC markedly reduced the diameter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…An explanation for this phenomenon is that introducing the wood flour, which is highly hydrophilic in nature [25,26] into the WPVC makes the PVC become more hydrophilic. As a consequence, more water molecules can be absorbed into/onto the HPQM/WPVC surfaces [19]. Another possible reason was that the methoxy groups (-OCH 3 ) in the aminosilane could be hydrolyzed to produce silanol [-OSi(OH) 3 ] and these silanol groups would develop covalent siloxane bonds by reaction with OH groups of wood during the wood flour pretreatment process, and then the PVC could bond with the amine group of aminosilane modified wood flour by an acid-base interaction [27][28][29].…”
Section: Results and Discussion 31 Effects Of Hpqm And Wood Flour Cmentioning
confidence: 99%
See 2 more Smart Citations
“…An explanation for this phenomenon is that introducing the wood flour, which is highly hydrophilic in nature [25,26] into the WPVC makes the PVC become more hydrophilic. As a consequence, more water molecules can be absorbed into/onto the HPQM/WPVC surfaces [19]. Another possible reason was that the methoxy groups (-OCH 3 ) in the aminosilane could be hydrolyzed to produce silanol [-OSi(OH) 3 ] and these silanol groups would develop covalent siloxane bonds by reaction with OH groups of wood during the wood flour pretreatment process, and then the PVC could bond with the amine group of aminosilane modified wood flour by an acid-base interaction [27][28][29].…”
Section: Results and Discussion 31 Effects Of Hpqm And Wood Flour Cmentioning
confidence: 99%
“…Fungal growth inhibition [19] against A. niger, a testing fungus, was used for anti-fungal evaluation of specimens. The procedure was commenced by preparing an initial fungal spore suspension containing 10 4 spores/mL in 100 mL of 1:1 potato dextrose broth (PDB)/potato dextrose agar (PDA).…”
Section: Evaluation Of Fungal Growth 241 Fungal Growth Inhibition mentioning
confidence: 99%
See 1 more Smart Citation
“…This illustrated that the wood in WPC materials was in fact susceptible to biodeterioration . Thereafter, many researches were carried out to test the biological durability of WPCs, and subsequent studies clearly showed that WPC materials were susceptible to biodegradation …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that various decay fungi significantly affect the wood in WPCs. The result is a substantial loss of weight and strength of WPCs after exposure to decay fungi . Attack by mold fungi does not always deteriorate the mechanical and physical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%